Phytochemical and Trace Metal Analysis of Agave Leaves Used in Cosmetics from KwaZulu-Natal, South Africa - Achilonu, Matthew C.; Mkhize, Ntombikayise G.; Nkosi, S’busiso M.; Ngubane, Xolile V. (Asian Journal of Chemistry, 2026)
The global preference for natural, bioactive cosmetics has increased interest in plant-based ingredients rich in phytochemicals and essential trace minerals. This study examined the phytochemical composition and trace metal content of Agave angustifolia (AA) and Agave sisalana (AS) leaves from KwaZulu-Natal, South Africa, to evaluate their potential as raw materials for cosmetics. Methanolic leaf extracts were analysed both qualitatively and quantitatively for phytochemical components using UV-visible spectrophotometry, while functional groups were characterised by Fourier-transform infrared spectroscopy (Agilent Cary 630 FTIR). Trace metal levels were measured with inductively coupled plasma mass spectrometry (Perkin-Elmer NexION® 350 X ICP-MS). Qualitative screening confirmed the presence of key phytochemical classes, including flavonoids, saponins, tannins and phenolic compounds. Quantitative tests showed high levels of phenolics (AA: 771 ppm; AS: 691 ppm), flavonoids (AA: 1280 ppm; AS: 1895 ppm) and tannins (AA: 1378 ppm; AS: 1963 ppm), indicating strong antioxidant potential. Low ascorbic acid levels (0.09-0.13 ppm) suggest limited vitamin C contribution. The high phenolic and flavonoid contents imply the extracts possess significant antioxidant, anti-inflammatory and antimicrobial properties, making them suitable for formulations targeting photoageing, irritation and acne-prone skin. ICP-MS analysis identified eleven trace elements (As, Cd, Co, Cr, Cu, Mo, Ni, Pb, Sb, Se, Zn), including essential micronutrients (Zn, Cu and Se), which support collagen synthesis, wound healing and antioxidant defence. The analysis also identified skin sensitizers such as Co and Cr, along with toxic elements like Cd and As, though their levels remained within regulatory limits. However, Pb and Ni were found to slightly exceed the permissible limits set by the European Union and Health Canada. These findings highlight the phytochemical richness and mineral diversity of A. angustifolia and A. sisalana, supporting their potential as multifunctional bioactive ingredients in natural cosmetic formulations, provided they are carefully sourced and refined under safety standards.